Enhancement of Madrasah Students' Literacy through AKMI Program Integrated in Educational Curriculum - Novebri, Novebri; Samosir, Hottua (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
Curriculum refers to a comprehensive compilation of scientific disciplines studied systematically in an educational institution, which impacts increasing student proficiency. The Indonesian Madrasah Competency Assessment (AKMI) was introduced by the Indonesian Ministry of Religion in 2021 to evaluate educational progress and student achievement in the curriculum. AKMI can be included in every subject taught at school. This research aims to analyze the increase in literacy of madrasah students through the integrated AKMI program in the education curriculum. The research method used is survey research. Data was collected from an online assessment held by AKMI organizers at the 2022 national seminar of the KSKK Directorate of the Ministry of Agriculture of the Republic of Indonesia. The survey instrument used was AKMI questions, validated and proven reliable, with quantitative data analysis techniques using a descriptive approach. The research results show that AKMI is a tool for madrasa teachers to evaluate students' skills in achieving the goals outlined in the curriculum. By utilizing these results, teachers can identify areas that need improvement and implement strategies to improve learning outcomes. Then, integrate learning outcomes (CP) in the curriculum with competency achievements (CK) at AKMI during the learning process at MI, MTs, and MA-level madrasas. AKMI is not a curriculum but can be integrated into the curriculum.